PENGARUH ARUS KAS BEBAS, SET PELUANG INVESTASI, DAN STRUKTUR KEPEMILIKAN TERHADAP KEBIJAKAN DIVIDEN - Abiyu Jabbar Rulianto (2022)
This study was conducted to determine the effect of free cash flow, investment opportunitiy set, managerial ownership, and institutional ownership on dividend policies in non-financial sector companies registered in the Kompas100 index in the period 2018-2020. According to Law No. 40 of 2007, companies are required to reserve their profits and distribute dividends when net income is positive. However, in reality, many companies that have negative net income can pay dividends. Then, there are also companies that have positive net income that do not pay dividends. This is the basic phenomenon of this research. This study is a type of quantitative research that uses secondary data in the form of financial statements and company annual reports. The sampling method in this study uses purposive sampling to produce as many as 57 samples of non-financial sector companies. Data analysis techniques in this study used the selection test of panel data regression models, classical assumption tests, hypothesis tests, and multiple linear regression tests. Based on the results of data analysis it can be concluded that the free cash flow, investment opportunity set, managerial ownership, and institutional ownership do not have a significant influence on dividend policy.